Up Grading Learning: Implementasi Pembelajaran PAI melalui Pembinaan Pengawas di MTs Wilayah Binaan Bantul - Ening Yuni Soleh Astuti (Jurnal Pendidikan Madrasah, 2020)
The research aims to determine the quality of teachers of Bantul Regency in implementing learning after gaining supervision through the activities of up grading learning. The study uses action research methods, conducted in two cycles covering the planning, implementation, observation, and reflection stages. The expected impact in the action of this study was the improvement of teacher quality in teaching. The results concluded that the implementation of supervision coaching implemented in six phases is to convey objectives and motivate, present information, organize into study groups, guide groups of work and study, evaluate, and reward. Learning through grading learning models can improve teachers ' ability to teach and improve teacher knowledge of concepts in teaching. The provision of supervision coaching using a learning up grading learning model with 6 phases of longer face-to-face meetings and complete teaching materials will further improve the quality and ability of the teachers to carry out their learning.